Pretreatment of selected peels for polygalacturonase production by Aspergillus awamori CICC 2040: Purification and application in mango juice extraction. (September 2019) - Adedeji, Olajide Emmanuel; Ezekiel, Olufunke Oluseyi
Abstract: This study evaluated effects of alkaline and microwave pretreatments of orange and plantain peels on activity, stability and kinetic properties of crude and purified polygalacturonase produced by Aspergillus awamori, and its application in mango juice extraction. Activity of crude polygalacturonase obtained from the untreated, alkaline, microwave, and combined alkaline and microwave pretreated peels were 25.17, 38.46, 26.21 and 42.05 U/mL; and 26.04, 38.82, 26.72 and 44.98 U/mL for orange and plantain peels, respectively. Molecular weight, saturation constant and maximum velocity for crude polygalacturonase were 30.00–96.20 kDa, 29.41–40.00 U/mL and 0.212–0.320 mg/L, respectively; and 31.00–32.00 kDa, 55.55–90.91 U/mL and 0.722–0.909 mg/mL for purified polygalacturonase. Optimum pH and temperature were 4–5 and 45-55 °C for crude and purified polygalacturonase, respectively. Enzymatic extraction resulted in an increase in percentage yield of mango juice. Pretreatment of orange and plantain peels enhanced properties of polygalacturonase from Aspergillus awamori . Polygalacturonase was effective for juice extraction from mango. Highlights: Pretreatment of orange and plantain peels increased activity and stability of PG. Purification of crude PG was enhanced by pretreatment of the peels. Purified PG was effective for juice extraction from mango.